COGNITIVE ASPECTS OF SIMULTANEOUS INTERPRETING. - Ismatova Zarina Ahrorovna (Journal of new century innovations, 2024)
Abstract: This article presents a comprehensive analysis of the cognitive aspects of simultaneous interpreting and the cognitive mechanisms underlying simultaneous interpreting, a complex and demanding task.